Payments to Senior Corporation Executives - Baker, John C. (Quarterly Journal of Economics, 1945)
Public hostility towards “excessive payments” ' to corporation executives, 170. — Reasons for this hostility, 171. — Sources of information, 171. — Definition of terms, 172. — Nature of the data available, 172. — Dollar payments by large companies, 173. — Distribution of aggregate payments, 175. — Relation to sales and earnings, 177. — Relation to functions, 177. — Payments by smaller companies, 179. — Relation to sales and earnings, 181. — Relation to functions, 181. — Summary of conclusions, 182.